Demonstration Methods to Improve Intensive Reading Skills in 3rd-Grade Students - Muhammad Yusnan; Karim; Risman Iye; Asriani Abbas; Sumiaty (The Indonesian Institute of Science and Technology Research, 2022)
The problem in this study is how to improve intensive reading skills in Indonesian subjects using the demo method in 3rd-grade students. The purpose of this study was